Given (x-2) is a factor of ax^3 + ax^2 + ax - 42, find the value of a

let f(x) = ax^3 + ax^2 + ax - 42if x-2 is a factor of f(x), then by remainder theorem, f(2) = 0and:a(2)^3 + a(2)^2 + a(2) -42 = 08a + 4a + 2a - 42 = 014a = 42a = 3

Related Maths A Level answers

All answers ▸

∫ 4/x^2+ 5x − 14 dx


Find the exact solution, in its simplest form, to the equation 2ln(2x+1) - 10 = 0.


Differentiate y=x*ln(x^3-5)


Is the function f(x)=x^3+24x+3 an increasing or decreasing function?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences